Perbuatan Makar di Indonesia: Kebijakan Hukum & Ketentuan Penyidikan - Winson Winson; Abdurakhman Alhakim (Widya Yuridika, 2022)
Indonesia is a state of law, as mandated in the Indonesian constitution. And also Indonesia is a democratic country that upholds the sovereignty of the people, this is certainly inseparable from the problems that then arise by the people and the sovereign government, namely an act which is then carried out by a person or group of people to overthrow the sovereign government or commonly known as a crime. treason. In Indonesia, the crime of treason is something that often happens considering that Indonesia is a democratic country. So the purpose of this research is to find out the provisions of the investigation of the perpetrators of the crime of treason in Indonesia and the policy of criminal law against the perpetrators of the crime of treason in Indonesia. This study uses a normative juridical research method. And it is known that the crime of treason in Indonesia has been explained in the Criminal Code, which in article 104 of the Criminal Code concerning treason, in this case, has an explanation related to the objective and subjective elements of an act of treason so that some provisions on the applicable criminal law policy, in this case, This can be used to adjust to the act of treason committed by the perpetrator.